2016
DOI: 10.1007/s10029-016-1563-x
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic mesh to prevent parastomal hernia after end colostomy: a meta-analysis and trial sequential analysis

Abstract: PSH prevention with mesh when creating an end colostomy reduces the incidence of PSH, the risk for subsequent PSH repair and does not increase wound infections. TSA shows that the RIS is reached for the primary outcome. Additional RCTs in the previous context are not needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 40 publications
3
47
0
4
Order By: Relevance
“…In our study, as in previous reports, we did not register a significant increase in short‐term postoperative morbidity/mortality, hospital stay or reintervention rate with the placement of PSM . Patients with PSM presented a trend towards more local complications of the ostomy, but the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In our study, as in previous reports, we did not register a significant increase in short‐term postoperative morbidity/mortality, hospital stay or reintervention rate with the placement of PSM . Patients with PSM presented a trend towards more local complications of the ostomy, but the difference did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 77%
“…Interest in hernia surgery is increasing worldwide, with focus not only on treatment but also on prevention (by laparoscopy or an open approach) . Previous data from randomized clinical trials and meta‐analyses confirm the safety, efficacy and cost‐effectiveness of PSH prevention with a permanent synthetic mesh when creating an end‐colostomy . A recently published multicentre randomized trial (the STOMAMESH trial) analysed the placement of a prophylactic synthetic mesh for prevention of PSH .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve systematic reviews and meta-analyses have now been published regarding the use of prophylactic mesh during primary stoma creation [28][29][30][31][32][33][34][35][36][37][38][39]. All reviews have demonstrated a statistically significant risk reduction of PSH with the use of prophylactic mesh.…”
Section: Quality Of Evidence Low Strength Of Recommendation Nonementioning
confidence: 99%
“…This seems to be the case when the wording of four recently published meta-analyses on the prevention of parastomal herniation (PSH) is scrutinized [1][2][3][4]. These looked at 9 studies with 569 patients [1], 10 studies with 649 patients [2], 11 studies [8 randomized controlled trials (RCTs)] with 755 patients [3] and 7 studies with 451 patients [4], respectively. Some reviews included studies described as having a 'high risk of bias' [1,3], whilst another only included RCTs with a 'low risk' [4].…”
mentioning
confidence: 99%